(untitled) (Philologia, 2021)
In the music drama Medjulusko blago by Momcilo Nastasijevic, the boundary can be found in the concept of the form as well as of the content. We can see the poetic connection between this play and folk lyric songs and ballads in the motif structure and the mythical base. Neznanac (Stranger), as the creature on the road, crosses the boundaries in the quest for his identity. He ﬁnds Medjuluzje as a place on the frontier, between life and death, the clean and the unclean. The author is concerned with the birth and death of Neznanac, Bela (White) and their families. Two choirs – of young and old women represent the vague border between the wedding and the funeral. The motif of incest is also connected with the problem of marginal status, the period before culture. The death of Neznanac by jumping into the abyss is also a way of crossing the boundary. The boundaries organize the space and time of life and death in the mythical sense. This motif determines the genre, style and destinies of the characters in this play.